Chronic low-grade inflammation in patients with systemic sclerosis is associated with increased risk for arteriosclerotic cardiovascular disease - Heilmeier, Ursula; Feldmann, Daria; Leynes, Andrew; Seng, Magdalena; Jandova, Ilona; Keute, Marius; Kollert, Florian; Voll, Reinhard Edmund; Finzel, Stephanie (Frontiers in Medicine, 2024)
Background Vasculopathy is a hallmark of systemic sclerosis (SSc) putting patients at an increased risk of cardiovascular disease. Approximately 20–25% of all SSc patients show prolonged elevated C-reactive protein (CRP) levels and thus signs of chronic low-grade inflammation. While CRP−positivity is an independent predictor of cardiovascular disease in non-SSc populations, the relationship between CRP−positivity and cardiovascular health/atherosclerosis in SSc patients is only incompletely understood. Here, we aimed to assess (1) which general, SSc disease-specific and cardiovascular parameters are associated with CRP−positivity in a cohort of SSc patients with prolonged CRP elevations (CRP+ SSc group) relative to SSc patients without CRP elevations (CRP− SSc group). In addition (2), we aimed to investigate whether prolonged CRP−positivity in SSc patients is associated with a higher cardiovascular risk and an increased atherosclerotic burden. We also aimed to (3) identify via random forest classification modeling which combined cardiovascular and/or SSc-specific parameters could differentiate best between SSc patients with elevated CRP levels (the so-called “inflammatory SSc subtype”) and SSc patients without increased CRP levels. Methods Sixty-five SSc patients were recruited and assigned to the CRP+ SSc group (n = 20) if their CRP levels were > 5 mg/L in at least three half-yearly visits within 2 years before enrolment or to the CRP− SSc group (n = 45), respectively. All patients underwent an anamnesis, physical examination, blood draw, and bilateral carotid ultrasound in order to assess arteriosclerotic burden including the presence, number and height of plaques, and carotid intima–media thickness (CIMT) as well as lipid profiles. 10-year ASCVD risk was estimated via the ASCVD risk estimator plus. Statistical evaluation included Spearman’s correlations, logistic regression and random forest modeling under 5-fold cross-validation, and permutation testing to determine combinations of cardiovascular variables highly discriminatory for CRP−positivity. Results SSc groups showed comparable mean age, height, and extent of SSc organ involvement. Regarding cardiovascular health, CRP+ SSc patients exhibited a significantly altered HDL-, LDL-, and triglyceride profile (0.001 ≤ p ≤ 0.017) and a significantly higher 10-year ASCVD risk (p = 0.047), relative to CRP− SSc patients. Additionally, within the subgroup of CRP+ SSc patients, positive correlations between CRP levels and CIMT right (ρ = 0.657, p = 0.002) and mean CIMT left and right (ρ = 0.497, p = 0.026) were seen. Combined ROC models identified the four lipid components (HDL, LDL, total cholesterol, and triglycerides) or the SSc duration and ASCVD category to differentiate with high cross-validated ROC-AUCs (AUC: 0.83 ± 0.15, and AUC: 0.86 ± 0.09, p < 0.001) for prolonged CRP−positivity among SSc patients. Conclusion Our data indicate that persistent CRP−positivity and thus chronic low-grade inflammation in SSc patients enhance the risk for arteriosclerotic-cardiovascular disease significantly beyond the ASCVD risk observed for our SSc patients without CRP elevations. It seems to be along with a disrupted lipid profile the hallmark of a distinct “inflammatory” subgroup of SSc patients. However, large population-based studies and clinical trials in patients with SSc are needed to validate our findings in a prospective or interventional setting.